ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN DAN SERVICE KOMPUTER (Studi Kasus Aurora Computer Muaradua) - Sri Tita Faulina; Rika Bherta (Jurnal Informatika dan Komputer (JIK), 2018)
Computer Aurora Muaradua is a private company engaged in the sale and service of computers. In addition to selling computers, it also sells computer accessories such as flash drives, mice, keyboards, cartridges, printers, ink and others. This research was conducted to study, analyze and design problems related to the selection of appropriate strategies to be applied in Muaradua's AuroraComputer. The selection of this strategy uses SWOT analysis. SWOT analysis is the identification of various factors systematically to formulate strategies that exist in the Aurora Computer Muaradua. Based on the results of the Internal-External matrix in the SWOT analysis, the design of information systems for sales and computer services is expected to facilitate in managing computer sales and service transaction data and sales reports (information), so that the Aurora Computer of two computers produces a faster, more precise performance system and accurate